2021
DOI: 10.1021/acs.chemrestox.0c00523
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Metabolomic Assessment of Pesticide Exposure in Central Valley, California

Abstract: Pesticides are widely used in the agricultural Central Valley region of California. Historically, this has included organophosphates (OPs), organochlorines (OCs), and pyrethroids (PYRs). This study aimed to identify perturbations of the serum metabolome in response to each class of pesticide and mutual associations between groups of metabolites and multiple pesticides. We conducted high-resolution metabolomic profiling of serum samples from 176 older adults living in the California Central Valley using liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 92 publications
2
13
0
Order By: Relevance
“…Comparison of metabolites associated with DDT and its metabolites in worms and human plasma and CSF revealed similar changes in amino acids and metabolites of the inflammatory pathways ( Table S2, Supplementary Material ). The overlapping metabolic pathways indicate changes in drug metabolism pathways, as expected, and additionally, changes in metabolism of precursors of neurotransmitters, butanoate metabolism, and pyrimidine metabolism, which have been previously reported to be associated with exposure to DDT metabolites and organochlorine pesticides ( 125 , 126 ). The concordance between the species further strengthens the use of C. elegans as a model relevant to studying the metabolic effect of exposure to toxicants on human health.…”
Section: Discussionsupporting
confidence: 69%
“…Comparison of metabolites associated with DDT and its metabolites in worms and human plasma and CSF revealed similar changes in amino acids and metabolites of the inflammatory pathways ( Table S2, Supplementary Material ). The overlapping metabolic pathways indicate changes in drug metabolism pathways, as expected, and additionally, changes in metabolism of precursors of neurotransmitters, butanoate metabolism, and pyrimidine metabolism, which have been previously reported to be associated with exposure to DDT metabolites and organochlorine pesticides ( 125 , 126 ). The concordance between the species further strengthens the use of C. elegans as a model relevant to studying the metabolic effect of exposure to toxicants on human health.…”
Section: Discussionsupporting
confidence: 69%
“…The rise in the proportion of the aging population has led to an increase in age-related neurodegenerative disorders. Various metabolic pathways like fatty acid β-oxidation pathway, oxidative stress, mitochondrial dysfunction, glycerophospholipid metabolism, tryptophan metabolism, and glutathione metabolism have been shown to play a role in neurodegenerative diseases (Widner et al 2002;Jenner 2003;Smeyne and Smeyne 2013;Bose and Beal 2016;Yan et al 2021). The causative factors contributing to the onset and development of complex and multigenic neurodegenerative diseases have been attributed to genetic and environmental factors (Brown et al 2005;Cannon and Greenamyre 2013;Pihlstrøm et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides disrupt critical cellular mechanisms that sustain the metabolic requirements and activity of the nervous system (Keifer and Fireston 2007). Studies speculate that most Alzheimer's disease (AD) and Parkinson's disease (PD) cases observed in the older population might have been exposed to pesticides long before diagnosis (de Pedro-Cuesta et al 2015;Yan et al 2021). Furthermore, Freire and Koifman (2012) reviewed several published prospective and case-control studies and found evidence of an association between pesticide exposure and PD (Freire and Koifman 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations